2015
DOI: 10.1007/s10534-015-9823-2
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and metabolic syndrome: a review of experimental and clinical observations

Abstract: A significant interrelation between heavy metal exposure and metabolic syndrome (MetS) development has been demonstrated earlier. Despite the presence of a number of works aimed at the investigation of the role of Hg in MetS development, the existing data remain contradictory. Therefore, the primary objective of the current work is to review the existing data regarding the influence of mercury on universal mechanisms involved in the pathogenesis of the development of MetS and its components. The brief chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 232 publications
4
54
1
1
Order By: Relevance
“…Moreover, they observed 2-fold risk of intense myocardial infarction (AMI) and fatality from coronary heart disease (CHD) and cardiovascular disease (CVD) in male patients with an raised hair content of mercury (>2 μg/g) (Salonen et al 2000; Salonen et al 1995). Similar findings about associations between blood mercury level and hypertension and between blood mercury level and myocardial infarction were found in the other studies (Kim et al 2014; Valera et al 2013; Tinkov et al 2015). According to proven relationship between the content of mercury in the human body and cardiovascular disease, the observed higher content of Hg in patients taking medicines associated with this disease may be indicative that the drugs could be an additional source of this metal for human.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, they observed 2-fold risk of intense myocardial infarction (AMI) and fatality from coronary heart disease (CHD) and cardiovascular disease (CVD) in male patients with an raised hair content of mercury (>2 μg/g) (Salonen et al 2000; Salonen et al 1995). Similar findings about associations between blood mercury level and hypertension and between blood mercury level and myocardial infarction were found in the other studies (Kim et al 2014; Valera et al 2013; Tinkov et al 2015). According to proven relationship between the content of mercury in the human body and cardiovascular disease, the observed higher content of Hg in patients taking medicines associated with this disease may be indicative that the drugs could be an additional source of this metal for human.…”
Section: Discussionsupporting
confidence: 89%
“…Another probable mechanism of increased metal content in the organism during obesity can be impaired metal excretion, for mercury is biliary secretion (Skalnaya et al 2014). Besides, Park et al (2009) found that high mercury concentration in hair may indicate increased risk of metabolic syndrome, which is strongly associated with obesity (Tinkov et al 2015). This finding is consistent with the statement by Barbosa et al (2001), that factors, such as gender, age, and BMI, can modulate metabolism of nutritive and toxic metals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism of mercury-induced hepatotoxicity has not been clarified, some studies suggested that mercury produces reactive oxygen species and depresses antioxidant system components, and the resulting oxidative stress triggers hepatotoxicity [12, 13, 32]. In the present study, when we performed a mediation analysis for oxidative stress biomarkers, we could not find significant results in all of the participants or the non-drinker group.…”
Section: Discussioncontrasting
confidence: 77%
“…Decreased ATP production and oxidative stress are important factors in methyl mercury toxicity (Ally et al, 1984;Caito and Aschner, 2015). The general role of mercury and oxidative stress is nicely summarized in Tinkov et al (2015). Methyl mercuryinduced oxidative stress has been linked to mitochondrial dysfunction in a number of different cell types, including neurons, cardiomyocytes and kidney cells (Bourdineaud et al, 2011;Lu et al, 2011;Qu et al, 2013;Truong et al, 2015).…”
Section: Mitochondria and Oxidative Stressmentioning
confidence: 99%